THE CORRELATION BETWEEN BULLYING EXPERIENCE, STUDY HABITS, AND CRITICAL THINKING OF SOCIAL LEARNING IN HIGHER EDUCATION - Rasidi, Muhamad Ahyar; Nuruddin, Nuruddin; Ibrahim, Nurshahira (JURNAL EDUSCIENCE, 2025)
Purpose—This study aims to determine the relationship between bullying experiences and learning habits and critical thinking skills in social science learning in higher education.Methodology—This research is a correlational study with 90 samples. Data for the three variables of this study were collected through the distribution of Google Form questionnaires. Data analysis used multiple correlations, but the first prerequisite tests, including validity, reliability, normality, and homogeneity, were carried out.Findings—The research results show that bullying experiences and study habits significantly affect students’ critical thinking skills, where rcount> table or 0,865>0,2050 shows a positive relationship. Furthermore, the significance value is 0,000< 0.05, so the data shows a significant relationship between bullying experience, learning habits, and critical thinking. Maintaining and preserving appropriate study habits will prevent bullying, no matter how severe, from affecting your critical thinking ability.Contribution – This study provides important insights into how bullying experiences and learning habits significantly affect students' critical thinking skills. Thus, whatever the form of learning style, it contributes positively to developing critical thinking skills.